Public Investment in Human Capital and Economic Growth in Algeria: An empirical study using ARDL approach - Mohamed Ramli; Faiçal Boutayeba; Azzeddine Nezai (SocioEconomic Challenges)
The main aim of this research paper is to examine empirically the link between public investment in human capital and economic growth in Algeria over the period 1990-2017. In fact, public authorities spend annually considerable funds to make both education and health available for all citizens as they are vital elements for a better life. This political action which is well understood from social perspective should have also some economic benefits especially in terms economic growth. Scholars strongly argued the crucial importance of investing in human capital to spur growth. In this context, the current paper tends to assess the impact of public spending devoted to human capital components on economic growth in Algeria. To do so, the study used annual time series data of government expenditures on these two sectors ranged from 1990 to 2017, and employs for estimation the autoregressive distributed lag (ARDL) approach. The main finding of this paper is that there is no cointegrating relationship between these two variables in the long run. This result is in line with many previous studies in Algeria as well as in other developing countries. This basically supports the idea that spending on education and health would not inevitably lead to growth. The lessons learnt from the experience of emerging economies denote that there are a series of preliminary conditions that should be set up to make the association between public investment in human capital and growth possible. Government spending alone cannot induce economic growth if corruption prevails and resources are inefficiently allocated. Also, it is the quality of health and education that matters. In Algeria, despite of the considerable funding of education and health sectors, the quality of service offered inside schools and hospitals is still poor. Thus, increasing numbers of doctors leave the country because they believe that work conditions are not suitable. Many Patients also prefer to join foreign hospitals because they believe that local medical service is somewhat unsatisfactory. Likewise, a great number of university students choose to join foreign universities to pursue their higher studies because they consider the quality of local universities is poor. Based on this evidence, policymakers are invited to take into consideration these conditions among others in order to strengthen the impact of public investment in human capital on economic growth in the future.